Bar's closure ends long history (Raton, NM Raton Range, 1996)
This article is about the Silver Dollar Bar closing its doors after 61 years of business.
Newspaper article
Master list item #: 59
File location is in the Raton file Cabinet
Keywords: Musso, Lena -- Bar Owner; Musso, Charles; Argradi, Robert -- d. 1-22-1936; Gatti, Fred; Gatti, Perinda; San Roman, Gloria; Romero, Lucy; Silver Dollar Bar; 1-22-1938 Bar burned to the ground; Local Business; Property Changes; Bars; Family Business; Business Closings; Business History; Park Avenue; Raton, New Mexico